2011
DOI: 10.1002/hbm.21188
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human gustatory cortex by activation likelihood estimation

Abstract: Over the last two decades, neuroimaging methods have identified a variety of taste-responsive brain regions. Their precise location, however, remains in dispute. For example, taste stimulation activates areas throughout the insula and overlying operculum, but identification of subregions has been inconsistent. Furthermore, literature reviews and summaries of gustatory brain activations tend to reiterate rather than resolve this ambiguity. Here we used a new meta-analytic method [activation likelihood estimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
151
6
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(187 citation statements)
references
References 83 publications
(129 reference statements)
27
151
6
2
Order By: Relevance
“…Although taste stimulation has consistently activated the same brain regions across multiple f MRI studies, including insula and overlaying operculum, the transduction mechanisms remain incompletely characterised. Previous studies reported the primary taste cortex is located within the anterior insula/frontal operculum (13)(14)(15) with secondary projections to the orbitofrontal cortex (OFC) (16) , amygdala (17) , anterior cingulate cortex (ACC) (18) , ventral striatum (19) and dorsolateral prefrontal cortex (20) . O'Doherty et al were the first to investigate the cortical response to pleasant (glucose) and aversive (salt) taste stimuli by assessing stimuli against a tasteless control stimulus (21) .…”
Section: Functional Mri Responses To Taste Aroma and Oral Somatosensmentioning
confidence: 99%
“…Although taste stimulation has consistently activated the same brain regions across multiple f MRI studies, including insula and overlaying operculum, the transduction mechanisms remain incompletely characterised. Previous studies reported the primary taste cortex is located within the anterior insula/frontal operculum (13)(14)(15) with secondary projections to the orbitofrontal cortex (OFC) (16) , amygdala (17) , anterior cingulate cortex (ACC) (18) , ventral striatum (19) and dorsolateral prefrontal cortex (20) . O'Doherty et al were the first to investigate the cortical response to pleasant (glucose) and aversive (salt) taste stimuli by assessing stimuli against a tasteless control stimulus (21) .…”
Section: Functional Mri Responses To Taste Aroma and Oral Somatosensmentioning
confidence: 99%
“…Food intake is regulated by taste and smell,203, 204 and chemosensory dysfunction could influence dietary intake. Nordén et al .…”
Section: Compromised Dietary Intakementioning
confidence: 99%
“…Of course, once ingestion has started, gastrointestinal neural and hormonal signals also start to contribute. Summaries and detail on the basic processing of food stimuli in the brain can be found in several reviews and meta-analyses addressing visual food stimuli (food images) (9) , odour (10) , taste (11,12) and flavour (taste, odour and somatosensory stimulation) (13,14) . A well-known phenomenon driven by cephalic stimulation is sensory-specific satiety (15) .…”
Section: Food-brain Interactionmentioning
confidence: 99%